ROC and COPRAS Algorithms in a Decision Support System for Employee Career Assessment - Ritonga, Fazrul Umri; Fakhriza, M.; Harahap, Aninda Muliani (Information Technology and Science (ITScience), 2024)
PT. Union Confectionery, a long-established company in the confectionery production industry, had encountered significant challenges in managing employee career progression, including transfers, demotions, and promotions. The primary issue faced was the difficulty in conducting objective employee performance assessments and determining the appropriate criteria for career development. These assessments involved various complex factors such as work experience, discipline, education level, age, job performance, attendance, teamwork, and work ethics. To address these challenges, this study proposed the implementation of a web-based Decision Support System (DSS) utilizing the Rank Order Centroid (ROC) method for criteria weighting and the Complex Proportional Assessment (COPRAS) method for ranking decisions. The implementation of this system was expected to assist the management of PT. Union Confectionery in making more accurate and transparent decisions, while also improving employee satisfaction and operational efficiency. This research also compared previous studies that used similar methods for performance assessment, albeit with a narrower focus, specifically at the supervisory level. The findings from this study were anticipated to provide a comprehensive and innovative solution for employee career management across all levels of PT. Union Confectionery’s organization, as well as contribute to the development of more effective human resource management practices.